2011
DOI: 10.1111/j.1365-3040.2011.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite oxidase controls sulfur metabolism under SO2 exposure in Arabidopsis thaliana

Abstract: In the present study, the significance of sulfite oxidase (SO) for sulfite detoxification and sulfur assimilation was investigated. In response to sulfur dioxide (SO2) exposure, a remarkable expansion of sulfate and a significant increase of GSH pool were observed in wild-type and SO-overexpressing Arabidopsis. These metabolic changes were connected with a negative feedback inhibition of adenosine 5Ј-phosphosulfate reductase (APR), but no alterations in gas exchange parameters or visible symptoms of injury. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 58 publications
3
74
0
Order By: Relevance
“…Similarly, a 1.5-to 2-fold increase in SiR activity was recorded in Arabidopsis plants after relatively long-term fumigation with SO 2 for 60 h (Randewig et al, 2012).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Similarly, a 1.5-to 2-fold increase in SiR activity was recorded in Arabidopsis plants after relatively long-term fumigation with SO 2 for 60 h (Randewig et al, 2012).…”
mentioning
confidence: 67%
“…SO, like SiR, has been shown to be constitutively expressed in Arabidopsis plant organs, with relative enrichment in root tips and the vascular system (Brychkova et al, 2007;Lang et al, 2007;Khan et al, 2010;Randewig et al, 2012). Infiltration of sulfite by injection into plant leaves allowed us to demonstrate the rapid (within 30 min) inducibility of both SiR and SO expression.…”
Section: Interplay Between Sir and So In Sulfite Detoxificationmentioning
confidence: 90%
See 2 more Smart Citations
“…Their close vicinity to the chloroplasts (Oikawa et al, 2003) and mitochondria (Islam and Takagi, 2010) would enable the generation of a sulfite gradient facilitated by SOdependent sulfite oxidation (Hansch and Mendel, 2008). Indeed, application by fumigation of toxic SO 2 levels to normally grown Arabidopsis and tomato mutants, overexpressing or lacking SO activity, demonstrated the essential role of SO in protecting plant cell components from toxic sulfite (Brychkova et al, 2007;Lang et al, 2007;Randewig et al, 2012). By employing prolonged dark stress to induce the production of endogenous sulfite under conditions in which other sulfite network components are downregulated, we further demonstrated that peroxisomal SO serves as the major conduit of sulfite detoxification (Fig.…”
Section: Subcellular Localizations Of the Sulfite Network And Sulfitementioning
confidence: 99%